2020
DOI: 10.1519/jsc.0000000000002434
|View full text |Cite
|
Sign up to set email alerts
|

Effects on Volume Load and Ratings of Perceived Exertion in Individuals' Advanced Weight Training After Transcranial Direct Current Stimulation

Abstract: The aim of this study was investigate the effects of transcranial direct current stimulation (tDCS) on volume-load and ratings of perceived exertion. Fifteen young healthy individuals, aged between 20 and 30 years in advanced strength training were recruited. Test and retest of the 10 maximum repetitions (10RM) were performed to determine the reliability of load utilized. Subjects performed three experimental conditions in a randomized, double-blinded crossover design: anodic stimulation (a-tDCS), cathodic sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
92
0
12

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(108 citation statements)
references
References 26 publications
1
92
0
12
Order By: Relevance
“…tDCS has been used to uncover neural links between muscle strength and related brain areas through modulating their excitability. Accordingly, numerous studies have demonstrated tDCS related increases in muscle strength endurance [9][10][11] and MIVC [12][13][14], particularly for upper extremities. Lower extremity muscle strength modulation has also been assessed through tDCS application, although results are rather inconclusive.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…tDCS has been used to uncover neural links between muscle strength and related brain areas through modulating their excitability. Accordingly, numerous studies have demonstrated tDCS related increases in muscle strength endurance [9][10][11] and MIVC [12][13][14], particularly for upper extremities. Lower extremity muscle strength modulation has also been assessed through tDCS application, although results are rather inconclusive.…”
Section: Introductionmentioning
confidence: 99%
“…Lower extremity muscle strength modulation has also been assessed through tDCS application, although results are rather inconclusive. For example, some results showed tDCS to be effective in modulating isometric muscle strength [10,14,15], whereas other studies provide evidence to the contrary [16][17][18]. It is of note that, among others stimulation sites, current density (mA/cm 2 ), as well as strength training background of participants all differ between studies, making interpretations difficult.…”
Section: Introductionmentioning
confidence: 99%
“…Les améliorations chez les sujets sportifs confirmés étaient négligeables comparativement aux sujets sportifs récréationnels et sédentaires. Étonnamment, dans cette revue, nous avons retrouvé, de façon ponctuelle, des articles montrant des améliorations significatives et importantes après une seule séance de stimulation chez des sujets sportifs confirmés voire de haut niveau (un article a trouvé une amélioration de 35 % en moyenne par rapport au placebo [44]). Ce résultat est surprenant car les sujets avaient au préalable un niveau avancé en entraînement de la force.…”
Section: Discussionunclassified
“…This suggests that tDCS is not as effective as it appear to reduce perceived exertion. For instance, after an acute stimulation of the motor cortex in a cycling TTE [30], temporal cortex in a cycling incremental test [29] and prefrontal cortex in a resistance strength exercise [43], the authors found an improvement in physical performance accompanied by a reduction in the RPE in the anodal condition compared to the sham condition. Despite the different protocols used in these studies, all of them suggested that the reduction in RPE was as a consequence of tDCS affecting other brain areas, such as the insular cortex, which has been linked to autonomic regulation and to self-perception and awareness of body sensations [46].…”
Section: Discussionmentioning
confidence: 99%
“…Under the umbrella of cognitive load, we refer to those interventions aiming to induce different levels of cognitive (executive) load during a self-paced aerobic exercise. For instance, Epling et al [43] found that performing a word recall task involving working memory, while participants completed a self-paced outdoor running exercise, increased the mental workload (measured with the NASA-TLX scale) compared to running without performing any cognitive task. However, they did not find that the cognitive task performed during a 5-min self-paced run affected the distance covered by the 12 athletes.…”
Section: Cognitive Load During Self-paced Exercisementioning
confidence: 99%